2007
DOI: 10.1002/syn.20395
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the regulation of cocaine and amphetamine‐regulated transcript expression in hypothalamic nuclei of rats by forced swim stress

Abstract: Cocaine and amphetamine-regulated transcript (CART) peptides are suggested to play a role in several physiological processes including feeding, reward, neuroendocrine modulation, and the stress response. Although some studies implicate the modulation of CART peptide expression by glucocorticoids, direct evidence relating CART to the stress response is limited. The present study was undertaken to evaluate the possible involvement of CART peptides during acute stress in male and female rats. Forced swim was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 69 publications
4
18
0
Order By: Relevance
“…Further, chronic (20-day) cold stress in rats increased CART mRNA levels in the arcuate nucleus, again suggesting a role for CART peptides in energy expenditure and thermogenesis 134 . exposing male rats to forced swimming also increased CART peptide levels in the PvN 135 . In addition, acute and chronic restraint stress increased CART mRNA levels in the hippocampus and amygdala 136 and, conversely, adrenalectomy reduced CART levels in the hippocampal dentate gyrus — an effect that was reversed by corticosterone replacement.…”
Section: The Cart System and Stressmentioning
confidence: 84%
“…Further, chronic (20-day) cold stress in rats increased CART mRNA levels in the arcuate nucleus, again suggesting a role for CART peptides in energy expenditure and thermogenesis 134 . exposing male rats to forced swimming also increased CART peptide levels in the PvN 135 . In addition, acute and chronic restraint stress increased CART mRNA levels in the hippocampus and amygdala 136 and, conversely, adrenalectomy reduced CART levels in the hippocampal dentate gyrus — an effect that was reversed by corticosterone replacement.…”
Section: The Cart System and Stressmentioning
confidence: 84%
“…In rats, a sexually dimorphic modulation of CART expression was observed in the PVN and ARC nuclei with the forced swim test (Gozen et al 2007). Another study in rats showed that E administration reduced the elevated CART expression due to reoccurring insulin hypoglycemia.…”
Section: Effects Of E and P Administrationmentioning
confidence: 99%
“…This may at first seem surprising, but only subtle gender differences in CART levels emerge in eutherian brains even under particularly stressful forced swim experiences [Balkan et al, 2006;Gozen et al, 2007].…”
Section: Functional Significance Of Cart Distribution In Marsupialsmentioning
confidence: 99%